A primer on preaching helpful information to all who are interested in the preparation and presentation of the gospel message - Gibbs, Alfred Perks, 1890-1967 (Fort Dodge, IA Walterick)
Includes reprint of booklet by A.E. Horton : The teaching, interpretation amd application of Scripture
Brethren writer . Date of foreword 1939.
Keywords: Preaching